2020
DOI: 10.1186/s40902-020-00282-3
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular shape prediction using cephalometric analysis: applications in craniofacial analysis, forensic anthropology and archaeological reconstruction

Abstract: Background The human mandible is variable in shape, size and position and any deviation from normal can affect the facial appearance and dental occlusion. Objectives The objectives of this study were to determine whether the Sassouni cephalometric analysis could help predict two-dimensional mandibular shape in humans using cephalometric planes and landmarks. Materials and methods A retrospective computerised analysis of 100 lateral cephalometric radiographs taken at Kingston Hospital Orthodontic Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Identifying the growth spurt of maxilla and mandible is important for orthodontic treatment during the growth period. However, it is considered difficult to predict because of the various differences resulting from the growth spurt of height 10 . At present, carpal roentgens are regarded as the gold standard to assess bone maturation 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Identifying the growth spurt of maxilla and mandible is important for orthodontic treatment during the growth period. However, it is considered difficult to predict because of the various differences resulting from the growth spurt of height 10 . At present, carpal roentgens are regarded as the gold standard to assess bone maturation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, carpal roentgens are regarded as the gold standard to assess bone maturation 9 . In fact, there are several reports on the correlation between the ages determined using carpal bones and the cervical spine 10,[15][16][17] , while the British Orthodontic Society stated that there are uncertainty using carpal radiography in predicting patient's adolescent growth spurt 17 . Lateral cephalometric radiographs are indispensable for clinical orthodontic treatment planning and are often taken at the time of the first visit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has reported that CVM correlates with carpal bone age assessment and is also suitable for mandibular growth assessment. The mandibular bone’s size and timing of growth are important to achieve good intermaxillary relationships in orthodontic treatment [ 9 , 10 ]. However, to the best of our knowledge, only a few previous reports have investigated the growth of maxilla and mandible [ 11 14 ] in the Japanese population with an unclarified growth pattern.…”
Section: Introductionmentioning
confidence: 99%